The Homeopathic Approach to Drug-Induced Liver Injury (Homoeopathy for All, 2024)
Drug-induced liver injury (DILI),  a significant concern in modern  medicine, is commonly caused by  hepatotoxic medications such as  acetaminophen (Paracetamol). It can  manifest as either acute or chronic  liver damage, leading to symptoms  like jaundice, fatigue, abdominal  pain, nausea, and alterations in urine  and stool color. While conventional  treatments for DILI focus primarily  on the withdrawal of the offending  drug and supportive care, these  approaches are often insufficient, as  there are limited specific antidotes  available for most cases. This  necessitates the exploration of non conventional treatment options  like homeopathy to address the  root causes of DILI effectively.  Acetaminophen, the most frequent  cause of DILI, has been widely  studied for its hepatotoxic effects.  Research has shown that homeopathic  drugs like Carduus marianus and  Chelidonium majus, with their  potential to prevent paracetamol induced centrilobular necrosis,  vacuolization & macro-vesicular  fatty changes, inflammation,  and elevated serum markers like  SGOT, SGPT, bilirubin, etc., may  offer significant hepatoprotective  benefits. These remedies work by  counteracting macromolecular
Keywords: acetaminophen (Paracetamol); constitution